Electric properties of carbon-doped n-type _-FeSi2/p-type Si heterojunction diodes - Motoki Takahara; Tarek M. Mostafa; Ryuji Baba; Suguru Funasaki; Mahmoud Shaban; Nathaporn Promros; Tsuyoshi Yoshitake (My University, 2015)
Undoped and C-doped n-type β-FeSi2 thin films were epitaxially grown on p-type Si substrates by sputtering and their heterojunction diode performances were experimentally studied. The near-infrared photodetection, at a wavelength of 1.3 µm, in these heterojunction diodes was clearly improved as compared to the heterojunctions comprising undoped-β-FeSi2. From X-ray diffraction and Raman spectroscopic measurements, there were no evident structural differences between the undoped and C-doped films. C-doping hardly affects the crystallization and epitaxial growth of β-FeSi2. The enhancement in the diode performance by C-doping might be owing to C atoms terminating dangling bonds and compensating defects in β-FeSi2 crystals.
Keywords: Dangling bond; Semiconductor materials and interfaces